T cell awareness of paternal alloantigens during pregnancy - Tafuri, Anna; Alferink, Judith; Möller, Peter; Hämmerling, Günter J.; Arnold, Bernd (Science, 1995)
During pregnancy a semiallogeneic fetus survives despite the presence of maternal T cells specific for paternally inherited histocompatibility antigens. A mouse transgenic for a T cell receptor recognizing the major histocompatibility (MHC) antigen H-2Kb was used to follow the fate of T cells reactive to paternal alloantigens. In contrast to syngeneic and third-party allogeneic pregnancies, mice bearing a Kb-positive conceptus had reduced numbers of Kb-reactive T cells and accepted Kb-positive tumor grafts. T cell phenotype and responsiveness were restored after delivery. Thus, during pregnancy maternal T cells acquire a transient state of tolerance specific for paternal alloantigens.